Proton detection and breathing regulation by the retrotrapezoid nucleus - Guyenet, Patrice G. (2016)
Abstract We discuss recent evidence which suggests that the principal central respiratory chemoreceptors are located within the retrotrapezoid nucleus (RTN) and that RTN neurons are directly sensitive to [H+]. RTN neurons are glutamatergic. In vitro, their activation by [H+] requires expression of a proton-activated G protein-coupled receptor (GPR4) and a proton-modulated potassium channel (TASK-2) whose transcripts are undetectable in astrocytes and the rest of the lower brainstem respiratory network. The pH response of RTN neurons is modulated by surrounding astrocytes but genetic deletion of RTN neurons or deletion of both GPR4 and TASK-2 virtually eliminates the central respiratory chemoreflex. Thus, although this reflex is regulated by innumerable brain pathways, it seems to operate predominantly by modulating the discharge rate of RTN neurons, and the activation of RTN neurons by hypercapnia may ultimately derive from their intrinsic pH sensitivity. RTN neurons increase lung ventilation by stimulating multiple aspects of breathing simultaneously. They stimulate breathing about equally during quiet wake and non-rapid eye movement (REM) sleep, and to a lesser degree during REM sleep. The activity of RTN neurons is regulated by inhibitory feedback and by excitatory inputs, notably from the carotid bodies. The latter input operates during normo- or hypercapnia but fails to activate RTN neurons under hypocapnic conditions. RTN inhibition probably limits the degree of hyperventilation produced by hypocapnic hypoxia. RTN neurons are also activated by inputs from serotonergic neurons and hypothalamic neurons. The absence of RTN neurons probably underlies the sleep apnoea and lack of chemoreflex that characterize congenital central hypoventilation syndrome.